Design and validation of geography attitudinal scale (2020)
The aim of this study is to design, develop, validate and conduct reliability test of a questionnaire evaluating attitudes of students towards Geography. The questionnaire was analyzed using SPSS software version 21.0. The coefficient of crombach’s Alfa obtained from the instrument was 0.82. The instrument was also validated using exploratory factor analysis. It was observed that the underlying factors had total variance of 50.418% in the attitude of the students. Conclusively, the attitude Questionnaire towards Geography was found to be an appropriate instrument for a good study and measurement of student’s attitude towards Geography.